The Implementation of Contextual Language Learning Through Field Trip Activities in Arabic Vocabulary Learning - Thoyibah, Naim Hikmatut; Habibah, Nur Faiz; Buana, Ba'iq Kurnia (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the implementation of Contextual Language Learning through field trip activities in Arabic vocabulary (mufradat) learning at MTs Silahul Muslimin Banyuwangi, East Java. The research was conducted at the Tegaldlimo Village Hall area, which provides a contextual environment including gazebos, open fields, highways, rice fields, and a stadium. The method used is descriptive qualitative research with data collection techniques including observation, interviews, and documentation. The research subjects consisted of 18 students, teachers, and the principal. Data analysis employs the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that before the intervention, students experienced boredom, low motivation, and passivity in memorizing mufradat. However, implementing a field trip with the theme "Natural Beauty" significantly increased students' activeness and curiosity. Students felt a higher sense of engagement as the learning process felt like a recreational activity rather than a formal lesson. Despite minor weather challenges such as light rain, the availability of gazebos ensured the learning process remained efficient. The study concludes that field trip activities transform a monotonous atmosphere into an enjoyable, game-like experience, enhancing students' confidence in identifying Arabic terms in a real-world environment. This approach makes the learning process more contextual, meaningful, and effective for junior high school students.